Kemampuan Penguasaan Materi Pelajaran Guru SMA/MA Berdasarkan Hasil Ujian Nasional Rendah - Fahmi -- (Jurnal Pendidikan dan Kebudayaan, 2013)
The purpose of this study is to determine the background and the ability to master the subject matter tested on the National Exam for the subject matter teachers of the high schools (SMA/MA). The subjects are high school teachers (SMA/MA)Â  in 100 districts/cities of 21 provinces throughout Indonesia that low achieving its National Exam. The number of sample schools sample is 10 schools in every districts/cities. Criteria for selection of sample schools are schools with graduation rates less than 80%, the average score is less than 6.5, the number of students a minimum of 300 students. Respondents are a sample of the grade 12 teachers SMA/MA study program of IPA and IPS for Indonesian Language, English, Mathematics, Physics, Chemistry, Biology, and Economics subjects. The instrument used is the National Exam tests and questionnaires. The results showed that 1) 90% teachers of high school (SMA/MA) with the academic background of D4 or S1, 6% S2, 1% D1 or D2 , and 3% D3; 2) mastery of the subject matter competency of teachers SMA/MA for IPA program, the lowest score is Biology (20.77)and the highest score is Indonesian Language (92.00); for IPS program,Â  the lowest score is Mathematics (33.33) and the highest score is Indonesian Language (82.00), 3) As many as 87% of teachers teach according to their educational background, 33% of teachers never follow MGMP and 29% of teachers rarely follow MGMP, and 38% of teachers not attended the training in accordance with the subject matter.